Bear and Bird. The stick and other stories [book with audioplayer] - Jarvis, 1985- (Jarvis, 1985- Bear and Bird., 2025)
"Bear and Bird are the kind of friends who just want to make each other happy. So when Bird realizes Bear has had a leaf stuck to his face all day, she goes to comical extremes not to embarrass him--even if it means encouraging a new trend. And when they both grab the same excellent stick on a windy day, they outdo each other trying to give it back--until Bear comes up with a better use for their imagination. Whether following a hilariously--and touchingly--circular path on Swapsy Day or discovering there are as many times of day as there are things to do, Jarvis's classic pair fuses humor and heart in another quartet of adventures."--